Role of genetic variation in the human sodium–glucose cotransporter 2 gene (SGLT2) in glucose homeostasis. (August 2011) - Enigk, Uta; Breitfeld, Jana; Schleinitz, Dorit; Dietrich, Kerstin; Halbritter, Jan; Fischer-Rosinsky, Antje; Enigk, Beate; Müller, Ines; Spranger, Joachim; Pfeiffer, Andreas; Stumvoll, Michael; Kovacs, Peter; et al.
Aims: Mutations in the sodium–glucose cotransporter 2 ( SGLT2 ), as well as treatment with SGLT2 inhibitors result in reduced fasting glucose levels, HbA1c and BMI. We therefore investigated the effects of common genetic variation in SGLT2 on human Type 2 diabetes and related traits.Materials & methods: Four HapMap tagging SNPs covering the common genetic variation in SGLT2 (r2 > 0.8 and minor allele frequency >0.01) were genotyped for subsequent association studies on BMI, Type 2 diabetes and related metabolic traits in 1013 Sorbs (Germany). An independent cohort from Berlin (n = 2042) was taken for replication.Results: The rs9934336 G-allele was nominally associated with increased 30-min plasma glucose, 120-min insulin concentrations and AUC120minglucose during oral glucose tolerance test in 907 nondiabetic Sorbs (p < 0.05). In the combined analysis including the Sorbs and the Berlin cohort, rs9934336 was nominally associated with 120-min insulin concentrations (adjusted p < 0.05) in nondiabetic subjects (n = 2590).Conclusion: Our data suggest a role of SGLT2 genetic variation in the regulation of glucose homeostasis and promote pharmacogenomic studies to clarify the efficacy of antidiabetic treatment by SGLT2 inhibitors. Original submitted 2 March 2011; Revision submitted 22 April 2011